The bronchoscopic probe-based confocal laser endomicroscopy to diagnose diffuse parenchymal lung diseases - Reichenberger, Frank; Silbernagel, Edith; Lindner, Michael; Stacher-Priehse, Elvira; Dinkel, Julien; Stepp, Herbert; Gesierich, Wolfgang; Behr, Juergen (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Diagnosis of diffuse parenchymal lung disease (DPLD) is based on clinical evaluation, radiological imaging and histology. However, additional techniques are warranted to improve diagnosis. Aims and objective: Probe based confocal laser endomicroscopy (pCLE) allows real time in vivo visualisation of the alveolar compartment during bronchoscopy based on autofluorescence of elastic fibres. We used pCLE (Cellvizio®, Mauna Kea Technology. Inc, Paris, France) to characterise alveolar patterns in patients with different types of DPLD.Methods: In this pilot study we included 42 therapy naive patients (13 female, age 72,6 +/- 2,3 years), who underwent bronchoscopy for workup of DPLD. pCLE images were obtained during rigid bronchoscopy in affected lung segments according to HR-CT scan, followed by cryobiopsies in the identical area. Diagnoses were made by a multidisciplinary panel.The description of pCLE patterns based on the degree of distortion of the hexagonal alveolar pattern, the density of alveolar structures, the presence of consolidations or loaded alveolar macrophages (AM). The assessment was performed by 2 investigators blinded for the final diagnosis.Results: The normal lung showed a typical alveolar loop pattern. In amiodarone lung disease loaded AM were predominant. COP showed characteristic focal consolidations. IPF was characterized by significant distortion and destruction, NSIP showed significant increase in density, and chronic HP presented with consolidations, mild distortion and density.Conclusion: pCLE shows potential as an adjunctive bronchoscopic imaging technique in the differential diagnosis of DPLD. Structured and quantitative analysis of the images is required.